Interactionist labeling: formal and informal labeling’s effects on juvenile delinquency - Kavish, Daniel Ryan (Crime & delinquency, 2016)
This article critically reviews prior labeling theory research concerning juvenile delinquency and crime, and proposes a new study using a recent data set. The labeling perspective is outlined as it was originally presented, and the theoretical elaborations that have taken place since are highlighted. Distinctions are made between formally applied criminal justice labels and the informal labels that are applied by educational institutions, significant others, and parental figures. An interactionist labeling model is presented to explain levels of juvenile delinquency among a nationally representative sample of American adolescents: the first three waves of the National Longitudinal Study of Adolescent Health (Add Health). Finally, negative binomial regression models are estimated to better explain the dynamic relationship between labels and delinquency. Consistent with labeling theory, formal labeling significantly increased future delinquency.